Prepare your talent for tomorrow. Issue 3 (13th June 2016) - Willyerd, Karie; Mistick, Barbara
Abstract : Purpose: According to the research conducted by the authors, the number one fear of employees around the world is that of becoming obsolete. The purpose of this article is to review five practices that employees can use to stay up to date and what organizations can do to support those practices. Design/methodology/approach: The authors' research mission was to discover how changes in the global economy and shifting demographics will impact the employment and talent marketplace. They collaborated with SAP SuccessFactors. Oxford Economics to conduct twin studies of 5, 500 executives and employees across 27 countries to find out what the future workforce is thinking, wanting and worrying over. In addition to the global surveys, they interviewed and spoke to over 300 people, and consulted with dozens of academic or corporate learning experts to refine and validate their five practices that employees and organizations can use to prepare for tomorrow. They also reviewed over 1, 000 academic papers or texts to support their conclusions. Findings: The five practices to stay prepared for tomorrow are: Learn on the fly: maximize the opportunities you already have to learn while working: be open: do not let opportunities pass you by: build a diverse network: understand what kind of a network is best for advancing a career. Be greedy about experiences: learn how to be strategic in choosing assignments and projects. Bounce forward: recover from setbacks and failures to stay motivated about your career. Originality/value: Career advice for the modern age is sorely lacking. The authors are both graduates of the scholar/practitioner doctoral program at Case Western Reserve University. As a result, a great value of this article is the bridge between solid research and practical advice. Additionally, the example strategies are included at two levels – for the employee and the organization.